Double-boiled linseed and mustard oil-based formulations to prepare oil-coated controlled release fertilizers - SARKAR, ABHIJIT; BISWAS, DIPAK RANJAN; DATTA, SAMAR CHANDRA; DWIVEDI, BRAHMA SWARUP; KUMAR, RAJESH; BANDYOPADHYAY, KALI KINKAR; BHATTACHARYYA, RANJAN; SAHA, MADHUMONTI; BISWAS, SIDDHARTHA SANKAR; PATRA, ASHOK KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Controlled nutrient release is one of the best fertilizer management options to enhance nutrient recovery efficiency and minimize environmental pollution. The research was conducted at Division of Soil Science and Agricultural Chemistry, ICAR-Indian Agricultural Research Institute, New Delhi during 2019-20 with the aims to formulate four oil-based formulations from different combinations of double-boiled linseed (Linum usitatissimum) and mustard (Brassica juncea) oils for coating diammonium phosphate (DAP) and to assess nitrogen (N) and phosphorus (P) release from them against uncoated DAP. Results revealed that oil-based formulation with 100 wt% linseed oil (Oil- 4 formulation) showed maximum variation in weight over the 30 days of curing; whereas, oil-based formulation containing 25 wt% linseed oil + 75 wt% mustard oil (Oil-1 formulation) had lowest variation in weight during curing. The N and P release pattern from oil-based formulations of coated DAP over 30 days in water medium with reference to uncoated DAP revealed that Oil-1 coated DAP formulation released lesser quantities of N and P than Oil-2 coated DAP; while 8% levels of coating material released lesser N and P than the 4% levels of coating. Compared to First-order kinetics model, the N and P release data were better fitted to Korsmeyer-Peppas model, which revealed that nutrient release from uncoated DAP followed Quasi-Fickian diffusion. Except 8%-Oil-2-DAP, all the oil-based formulations of coated DAP followed anomalous (Non-Fickian) diffusion. Thus, it may be concluded that double-boiled linseed and mustard oil-based formulations (Oil-1 formulation) of coated DAP could be an alternative option to produce cost effective controlled release fertilizers.